Potential of Palm Oil Solid Waste as Steam Power Fuel (Case Study at XYZ Palm Oil Mill) - Istianto Budhi Rahardja; Zati Daraquthni; A I Ramadhan (Journal of Applied Sciences and Advanced Technology, 2019)
The company's Palm Oil Mill (PKS) that produces the main products are Crude Palm Oil (CPO), Palm Kernel Oil (PKO) while the byproducts are solid waste in the form of fiber, shells, and Empty Fruit Bunches. Palm oil mill solid waste in the form of fiber and shells has the potential to become fuel for Steam Power Plants (PLTU). Fresh Fruit Bunch (TBS) Material Balance from Palm Oil Mill production output: Shells: 7%, Fiber: 13%, Empty bunches: 22% which can generate the total available Heat Calor of 28.936×106 Kcal / hour, and Total Total Power can be generated as much as 3.9 MW from the Palm Oil Mill Solid Waste which produces a thoughtput of 50 Tons / hour.